Получение 123 I по реакции 122Te(d,n) для радиофармацевтики - Агалаков Ю. В.; Большаков А. М. Алексей Михайлович; Гарапацкий А. А. Александр Александрович; Головков В. М. Владимир Михайлович; Комов А. И. Александр Иванович; Шеин В. В. (2007, 2007)
В фонде НТБ ТПУ отсутствует